(untitled) (Journal of Rashid Latif Medical College, 2025)
Background: Diabetic peripheral neuropathy (DPN) is a prevalent and severe complication of diabetes mellitus, resulting in high morbidity in the form of foot ulcers, amputations, and reduced quality of life. Early detection and management of risk factors can reduce its burden. Objective: To evaluate the prevalence of diabetic peripheral neuropathy (DPN) and determine its risk factors. Methodology: This descriptive cross-sectional study was carried out at the Diabetic Clinic, Department of Medicine, Arif Memorial Teaching Hospital, Lahore, from January 2023 to December 2023. Consecutive sampling was used to enroll 200 diabetic patients. Demographic information, clinical history, blood pressure, and blood glucose levels were noted. All the participants were recommended HbA1c and lipid profile. DPN was evaluated by the Michigan Neuropathy Screening Instrument (MNSI), and the data were statistically analyzed. Results: Among 200 patients, DPN was diagnosed in 83 patients (41.5%). Significant associations were found with increased duration of diabetes, hypertension, hyperglycemia, and pre-diabetes. Conclusion: DPN prevalence continues to be high among diabetic patients. Early detection, strict control of glycemia, and treatment of related risk factors are the keys to avoid this disabling complication.